A Brief Measure of Work Environment for Human Service Organizations. Issue 5 (20th October 2021) - Janczewski, Colleen E.; Mersky, Joshua P.; Plummer Lee, ChienTi
ABSTRACT: Organizational characteristics are important predictors of workplace outcomes, but the length and complexity of validated instruments restrict their use in research and practice. This study tested a brief Measure of Work Environment (MWE) using data from 718 child welfare and 349 home visiting professionals. Results confirmed a three-factor structure: group cohesion, leadership support, and organizational justice. The MWE demonstrated acceptable internal consistency (α = .87) and was significantly associated with job satisfaction, burnout, and intent to leave. The MWE is a promising, pragmatic measure of organizational environment for implementation research and program improvement.